Modification of Wnt signaling pathway on paraquat-induced inhibition of neural progenitor cell proliferation. (November 2018) - Zhao, Lina; Yan, Mengling; Wang, Xinjin; Xiong, Guiya; Wu, Chunhua; Wang, Zhibin; Zhou, Zhijun; Chang, Xiuli
Abstract: Paraquat (PQ) is an agricultural chemical used worldwide. As a potential neurotoxicant, PQ adversely affects neurogenesis and inhibits proliferation of neural progenitor cells (NPCs). However, the molecular mechanistic insights of PQ exposure on NPCs remains to be determined. Herein, we determine the extent to which Wnt/β-catenin signaling involved in the inhibition effect of PQ on mouse NPCs from subventricular zone (SVZ). NPCs were treated with different concentrations of PQ (40, 80, and 120 μM). PQ exposure provoked oxidative stress and apoptosis and PQ inhibited cell viability and proliferation in a concentration-dependent manner. Significantly, PQ exposure altered the expression/protein levels of the Wnt pathway genes in NPCs. In addition, PQ reduced cellular β-catenin, p-GSK-3β, and cyclin-D1 and increased the radio of Bax/Bcl2. Further, Wnt pathway activation by treatment with LiCl and Wnt1 attenuated PQ-induced inhibition of mNPCs proliferation. Antioxidant (NAC) treatment alleviated the inhibition of PQ-induced Wnt signaling pathway. Overall, our results suggest significant inhibitory effects of PQ on NPCs proliferation via the Wnt/β-catenin signaling pathway. Interestingly, our results implied that activation of Wnt/β-catenin signaling pathway attenuated PQ-induced autophagic cell death. Our results therefore bring our understanding of the molecular mechanisms of PQ-induced neurotoxicity. Highlights: PQ exposure provoked oxidative stress and inhibited NPCs proliferation. PQ inhibited NPCs proliferation via the Wnt/β-catenin signaling pathway. Activation of Wnt pathway attenuated PQ-induced autophagic cell death.